2020
DOI: 10.1101/2020.11.06.370858
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nanopanel2 calls phased low-frequency variants in Nanopore panel sequencing data

Abstract: Clinical decision making is increasingly guided by accurate and recurrent determination of presence and frequency of (somatic) variants and their haplotype through panel sequencing of disease-relevant genomic regions. Haplotype calling (phasing), however, is difficult and error prone unless variants are located on the same read which limits the ability of short-read sequencing to detect, e.g., co-occurrence of drug-resistance variants. Long-read panel sequencing enables direct phasing of amplicon variants besi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…While variant calling on long reads is still scarce, some studies reported at least comparable performance between them and conventional short reads-based pipelines (Orsini et al, 2018;Alkanaq et al, 2019;Greig et al, 2019;Wood et al, 2019;Magdy et al, 2020). Furthermore, new instruments for specific purposes have been devised recently, such as Nanopanel2 for identifying low-frequency somatic polymorphisms (Popitsch et al, 2020) or NanoVar for characterizing structural variations in low-depth sequencing data (Tham et al, 2020). However, in the studies mentioned, a single instrument was used, namely, PacBio's SMRTtools (Alkanaq et al, 2019), Nanopolish (Orsini et al, 2018;Greig et al, 2019;Magdy et al, 2020), or Varscan (Wood et al, 2019); thus, virtually no guidelines for choosing an optimal caller have been proposed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While variant calling on long reads is still scarce, some studies reported at least comparable performance between them and conventional short reads-based pipelines (Orsini et al, 2018;Alkanaq et al, 2019;Greig et al, 2019;Wood et al, 2019;Magdy et al, 2020). Furthermore, new instruments for specific purposes have been devised recently, such as Nanopanel2 for identifying low-frequency somatic polymorphisms (Popitsch et al, 2020) or NanoVar for characterizing structural variations in low-depth sequencing data (Tham et al, 2020). However, in the studies mentioned, a single instrument was used, namely, PacBio's SMRTtools (Alkanaq et al, 2019), Nanopolish (Orsini et al, 2018;Greig et al, 2019;Magdy et al, 2020), or Varscan (Wood et al, 2019); thus, virtually no guidelines for choosing an optimal caller have been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, long reads have found application in revealing structural variants (Aganezov et al, 2020), phasing analysis with haplotype reconstruction (Maestri et al, 2020;Popitsch et al, 2020), and the nanoporebased assay for analyzing leukemic samples (Orsini et al, 2018;Cumbo et al, 2019). Nevertheless, reports on long reads' usage with regard to mitochondrial genetics are still scarce.…”
Section: Introductionmentioning
confidence: 99%